Two coins, multiple sides: Rising powers and security assistance to Africa - Seabra, Pedro (8th European Conference on African Studies (ECAS), 2019)
Studies over the role of rising powers in providing security force assistance (SFA) to Africa have so far focused on ad hoc efforts led by either China, India, or Brazil. But despite their increased juxtaposition on the ground, the content of the expertise and capabilities offered remains insufficiently explored. What different solutions, if any, are indeed provided? And how does the record of rising powers fare against previous experiences deployed across the continent? Brazilian and Chinese efforts in Namibia as well as Chinese and Indian overtures towards Mozambique are here brought up in order to explore such predicaments. I evidence key similarities and distinctions in providing security capacity-building and demonstrate a similar exposure to past obstacles faced by other SFA actors in Africa.